2017
DOI: 10.1080/17435390.2016.1275866
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of fate and toxicity of selenite, biogenically, and chemically synthesized selenium nanoparticles to zebrafish (Danio rerio) embryogenesis

Abstract: Based on the data, it is contented that the presence of humic acid like substances of EPS on the surface of nano-Se b plays a major role in lowering the bioavailability (uptake) and toxicity of nano-Se b by decreasing the interactions between nanoparticles and embryos.ARTICLE HISTORY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 60 publications
(79 reference statements)
0
28
0
Order By: Relevance
“…The EPS had lowered bioavailability and toxicity by decreasing interactions between the Se NPs and fish embryos. [171] On the contrary, an environmental corona may also elevate the bioavailability of ENMs in fish. [172] For instance, surfactants (i.e., polysorbate 20, polysorbate 80, and SDS) exhibited synergistic toxicity with Au NPs in embryonic D. rerio, probably due to the increased bioavailability of surfactants by transport and internalization of the Au NPs.…”
Section: (10 Of 23)mentioning
confidence: 99%
“…The EPS had lowered bioavailability and toxicity by decreasing interactions between the Se NPs and fish embryos. [171] On the contrary, an environmental corona may also elevate the bioavailability of ENMs in fish. [172] For instance, surfactants (i.e., polysorbate 20, polysorbate 80, and SDS) exhibited synergistic toxicity with Au NPs in embryonic D. rerio, probably due to the increased bioavailability of surfactants by transport and internalization of the Au NPs.…”
Section: (10 Of 23)mentioning
confidence: 99%
“…There is no permissible limit for selenium prescribed by national and international agencies. But several pieces of research have reported selenium toxicity in the aquatic environment [25][26][27][28]. Selenium is released from weathering of selenium-rich rocks and soil that enter into surface water through surface runoff.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the exploitation of microorganisms able to bioconvert Se-oxyanions to Se 0 has emer ged as a cost-effective green alternative strategy for the decontamination of Se-polluted environments, with a particular focus on surface waters and wastewaters. To date, Se-bioremediation approaches exploit bacterial strains capable of reducing SeO 4 2− and SeO 3 2− [23] either to conserve energy [61][62][63] or to detoxify their environmental niches [23]. Since Se-oxyanions bio-reduction under anoxic conditions is more characterized as compared to the aerobic mode, mainly anaerobic bacterial strains have been used for Se-decontamination purposes [23].…”
Section: Bioremediation Of Se-polluted Environments Using Bacterial Pmentioning
confidence: 99%